Frequency of Metformin-Poor Response And Factors Associated With The Need For Insulin As A Complementary Treatment Among The Patients of Gestational Diabetes Mellitus - Iftikhar, Seher; Nawaz, Sobia; Syed, Shazia; Fatima, Fizza; Bibi, Saima; Malik, Sara (Journal of Rawalpindi Medical College, 2026)
Objective: The primary aim of this investigation was to determine the incidence of patients transitioning from metformin monotherapy to a combined regimen of insulin and metformin during the second or third trimester of pregnancy for managing gestational diabetes. Methods: This was a descriptive cross-sectional study conducted in the Department of Obstetrics and Gynecology at DHQ Hospital, Rawalpindi, from May 11, 2021, to May 10, 2022. This analysis involved 246 pregnant women aged between 20 and 35 years diagnosed with GDM during the first or second trimester of pregnancy and taking metformin mono-therapy. These women were followed, and a poor response to metformin was labeled as the need for supplemental insulin during the 2nd or 3rd trimester. Results: The mean age of the women was 26.6±4.6 years. The mean BMI of these women was 26.8±4.5 Kg/m2, and 43.5% of women were obese. Family history of diabetes was positive in 46.7% of women, while 28.0% of women had a history of GDM in a previous pregnancy. Poor response to metformin therapy was noted in 45 (18.3 %) women with GDM. Upon comparison, it was observed that the incidence of advanced maternal age (≥30 years) (53.3% vs. 23.4%; p-value<0.001), early onset of gestational diabetes mellitus (GDM) (gestational age ≤15 weeks) (77.8% vs. 46.8%; p-value<0.001), and obesity (62.2% vs. 39.3%; p-value=0.005) exhibited a statistically significant elevation among individuals with an inadequate response to metformin therapy, necessitating the inclusion of supplemental insulin. Conclusion: In the current study, we observed that a considerable proportion of pregnant women with GDM had poor response to metformin, and the frequency of older maternal age, early onset of GDM, and obesity was significantly higher among such cases, advocating that such women should be considered at higher risk of failure of metformin mono-therapy. Keywords: Gestational Diabetes, Metformin, Insulin, Treatment Outcome, Blood Glucose